2022
DOI: 10.1186/s12889-022-14455-4
|View full text |Cite
|
Sign up to set email alerts
|

Towards more personalized digital health interventions: a clustering method of action and coping plans to promote physical activity

Abstract: Background Despite effectiveness of action and coping planning in digital health interventions to promote physical activity (PA), attrition rates remain high. Indeed, support to make plans is often abstract and similar for each individual. Nevertheless, people are different, and context varies. Tailored support at the content level, involving suggestions of specific plans that are personalized to the individual, may reduce attrition and improve outcomes in digital health interventions. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However in order to develop digital interventions with more dynamic personalized suggestions, these associations should be embedded in a sort of computerized system to actually recommend suggestions to participants (Çelik Ertuğrul & Elçi 2020). Previous work from our research group already stated that the use of a knowledge-based system would be appropriate (Schroé et al 2022a). A knowledge-based system is a computer program that contains a knowledge base which represents knowledge in a particular domain (Pratiwi et al 2018) and reasons with that information via intelligent algorithms in order to deliver personalized suggestions.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However in order to develop digital interventions with more dynamic personalized suggestions, these associations should be embedded in a sort of computerized system to actually recommend suggestions to participants (Çelik Ertuğrul & Elçi 2020). Previous work from our research group already stated that the use of a knowledge-based system would be appropriate (Schroé et al 2022a). A knowledge-based system is a computer program that contains a knowledge base which represents knowledge in a particular domain (Pratiwi et al 2018) and reasons with that information via intelligent algorithms in order to deliver personalized suggestions.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work already investigated how personal user information (e.g. gender, age, motivational stage, etc) related towards the content of action and coping plans using a clustering method (Schroé et al 2022a). Although this approach was promising, this data was relatively stable over time and would only result in personalized suggestions at the level of the user pro le.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge only one study looked at characteristics of individuals that may predict the specific content of the PA plans made. Schroé et al (2022) found that female individuals, those with lower general levels of PA and those that were employed were more likely to create plans for household activities. Younger users were more likely to plan active transport and sport activities.…”
Section: Introductionmentioning
confidence: 99%